Shopify equity research - staying ahead of the market - Pais, José Pedro Fernandes de Azeredo (2020)
In this field lab project, we intended to perform a detailed breakdown of the company with the objective of being able to give out a recommendation on either buying, holding, or selling the security in question. We performed a detailed breakdown of the company’s historical reports as inputs to our model, where along with our research on the e-commerce market worldwide and with the pandemic bolstering it, we were able to build our discounted cash flow model. Additionally, e-commerce is a booming market which is growing year to year and we were able to better understand what drove this market and future prospects regarding its evolution.